2010
DOI: 10.1111/j.1540-8175.2009.01055.x
|View full text |Cite|
|
Sign up to set email alerts
|

High Prevalence of Rheumatic Heart Disease Detected by Echocardiography in School Children

Abstract: By echocardiographic screening, we found a high prevalence of rheumatic heart disease in the surveyed population. Clinical auscultation had much lower diagnostic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 11 publications
4
77
0
1
Order By: Relevance
“…We strongly believe that many subclinical RHD and asymptomatic CHD cases must have been missed in the early studies; since they were not screened by a cardiologist and echocardiogram not performed in all school children. Two recent echocardiographic studies by Bhaya et al 4 and Saxena et al 5 done in North India showed high prevalence of RHD varying from 20.4 to 51/1000. Overall prevalence of RHD in India varied from 1 to 51/1000.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We strongly believe that many subclinical RHD and asymptomatic CHD cases must have been missed in the early studies; since they were not screened by a cardiologist and echocardiogram not performed in all school children. Two recent echocardiographic studies by Bhaya et al 4 and Saxena et al 5 done in North India showed high prevalence of RHD varying from 20.4 to 51/1000. Overall prevalence of RHD in India varied from 1 to 51/1000.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of RHD varies across the globe, the highest being in subSaharan Africa (5.7e55.4/1000 6 ) with least being in the developed nations where the prevalence is less than 1/1000. In India the prevalence of RHD as reported (Table 4) by ICMR, 9,10 Padmavathi, 11 Grover et al, 10 Avasthi et al, 12 Patel et al, 13 Jacob Jose et al 2 Periwal et al, 14 Bhaya et al 4 and Saxena et al 5 varied from 1 to 51/1000. Jacob Jose from Vellore, 2 South India screened 2, 29 829 school children aged 6e18 years.…”
Section: Discussionmentioning
confidence: 97%
“…19 Use of echocardiography leads to detection and inclusion of previously unrecognized cases of subclinical carditis, the latter exists at rates up to 10 times higher than that diagnosed by examination alone. [20][21][22][23][24][25] Recently in 2012, World Heart Federation (WHF) proposed new criteria for echocardiographic diagnosis of RHD. 26 To the best of our knowledge, no studies were carried out to find out the echocardiography-based prevalence of RF/RHD in Bangladesh.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the persisting burden of the disease in some areas of the world echocardiography has been used in community studies in Mozambique and Cambodia (Marijon et al, 2007), Tonga (Carapetis et al, 2008), Nicaragua (Paar et al, 2010), Fiji (Steer et al, 2009;Reeves et al, 2011), Kenya (Anabwani et al, 1996), India (Thakur et al, 1996;Bhaya et al, 2010), Pakistan (Sadiq et al, 2009;Rizvi et al, 2004) and China (Zhimin 2006). These studies applied different inclusion and diagnostic criteria, raising the issue about the need for standardization of the definition of rheumatic heart valve disease by echocardiography.…”
Section: Recent Advances and Research Needsmentioning
confidence: 99%